Forestomach developmental failure in an 11-month-old Japanese Black steer with severely retarded growth and chronic ruminal tympany - ONO, Tetsushi (J Vet Med Sci, 2021)
This study reports findings from the pathological examination of the forestomach of an 11-month-old Japanese Black steer with severely retarded growth (41% of expected weight) and chronic ruminal tympany. The ruminal papillae were weakly formed (0.3–0.5 cm long) and unevenly distributed. The cellulae and cristae reticuli were underdeveloped; the cristae were 0.4–0.7 cm in height and milky white. The keratinized layer in the stratified squamous epithelium was thickened. Ruminal pH was 5.25, and ruminal volatile fatty acid concentration was 11.7 mM. The steer’s severely retarded growth was considered to be caused by malnutrition due to developmental and functional failure of the forestomach.